IMPROVING READING COMPREHENSION OF GRADE VIII STUDENTS AT SMP NEGERI 1 TOLITOLI THROUGH SCANNING TECHNIQUE - Rafi'i, Mohammad (Jurnal Madako Education, 2017)
The objective of the research is to prove whether the use of scanning technique is effective to improve students’ reading comprehension in narrative text. This pre-experimental study uses 30 students as a sample. They are grade VIIIG of SMP NEGERI 1 Tolitoli. The procedure of this research consists of pretest, treatment, and posttest. The result of the analysis shows that scanning technique contributes greatly to the students’ comprehension in narrative text. It can be seen by the difference of the mean score between pre-test and post-test. The mean score of pre-test is 65.27 while in the post-test improved up to 79.37. The data of this research are analyzed by using SPSS Program version 16.0. Then the data of both tests are analyzed by using T-test, and the result shows that the T-test value 9.795 is high than T-table value 2.045. It can be inferred that scanning technique is very effective to improve students’ reading comprehension in narrative text.  Keywords: Improving, reading comprehension, narrative text, scanning technique.